Development and Evaluation of a Candidate Inactivated Vaccine Against Bluetongue Virus Serotype 4 (BTV4) - Ljubisa Veljovic; Dimitrije Glisic; Marko Kirovski; Ljiljana Paušak; Vesna Milicevic (Vaccines, 2024)
Objectives: Although bluetongue is not a contagious disease, it is easily transmitted and spread by appropriate insect vectors, causing great economic damage. Climate change has led to the fact that vectors and diseases have spread to the top of Northern Europe, causing great economic losses in livestock production. An even greater problem is controlling the disease, because numerous species of domestic and wild ruminants are susceptible to bluetongue. The most effective tool against bluetongue disease is vaccination. Methods: Our goal was to carry out laboratory tests of the starting material and the finished product of the candidate inactivated vaccine against BTV4, and to comment on the obtained laboratory results and the results of previously performed clinical studies. There is no ideal vaccine against the bluetongue virus (BTV) due to the serotype diversity of its strains. Thus, there is a need for a vaccine for at least 24 clinically significant serotypes. Sometimes, it is difficult to obtain the desired amount of vaccine against a defined serotype on the market, and this has led to the need for a new vaccine against bluetongue disease. In this study, we tested an experimental inactivated vaccine against BTV4. The master seed BTV4 was examined and characterized by sequencing. Results: The candidate BTV4 vaccine induced the onset of immunity at the latest at day 21 after the application of the first dose in more than 80% of the vaccinated individuals, while the ELISA test detected specific antibodies against BTV for more than a year. Along with our laboratory results, the preliminary results of safety and efficacy trials are also presented. Conclusions: The side effects of this inactivated BTV4 vaccine are within the limits of permissible local reactions without generalized changes in the health status, while the serology and challenge test leads to the conclusion that this vaccine against BTV4 protects a high percentage of vaccinated individuals against BTV4 or causes a significant reduction in the intensity and duration of the clinical signs in the vaccinated sheep. Based on the trial results, the new vaccine has given encouraging results in terms of quality, safety, and preliminary efficacy tests. Thus, we believe that a new vaccine against BTV is on the horizon.